Revision of the Chinese Geotragus Schoenherr with description of three new species (Coleoptera: Curculionidae: Entiminae) - Ren, Li; Alonso-Zarazaga, Miguel A.; Zhang, Runzhi (Zootaxa, 2013)
The Chinese representatives of the entimine weevil genus Geotragus are here revised, including redescriptions of the two previously known species, G. himalayanus Boheman, 1845 and G. tuberculatus Chen, 1990, and descriptions of three new species from the Hengduan Mountains, Yunnan province, China: G. brevidens sp. nov., G. declivis sp. nov. and G. rugosus sp. nov.. Diagnostic characters of the genus, a key to Chinese species of Geotragus and a checklist of the now 11 known world species are also provided.